ANTI-INFLAMMATORY ACTIVITY OF CRUDE SAPONIN EXTRACTS FROM FIVE NIGERIAN MEDICINAL PLANTS - Hassan, H S; Sule, M I; Musa, A M; Musa, K Y; Abubakar, M S; Hassan, A S (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Crude saponin extracts of five medicinal plants used in the treatment of inflammatory diseases like rheumatoid arthritis, gout and haemorrhoids were screened for anti-inflammatory activity using carrageenan-induced rat paw oedema test. These plants were the whole plant of Schwenkia americana Linn (WSA), the rhizomes of Asparagus africanus Lam (RAA), the leaves of Dichrostachys cinerea Linn (LDC), the stem bark of Ficus iteophylla Miq (BFI) and the leaves of Indigofera pulchra Willd (LIP). A modify traditional method of crude saponins extraction was used to give the following percentage yields: WSA-2.74%, RAA-3.59%, LDC-1.62%, BFI-0.81% and LIP-1.57% respectively. Thin-layer chromatography was used to identify the type of saponins present in the extracts. The acute toxicity study of the crude saponin extracts in mice gave the following intraperitoneal LD50: WSA-471.2mg/kg, RAA- 1264.9mg/kg, LDC-1264.9mg/kg, BFI-118.3mg/kg and LIP-1264.9mg/kg respectively. The anti-inflammatory study of the extracts showed statistically significant (P<0.05) decreases in the rat paw-oedema as compared to the control. The percentage inhibitions of the extracts after four hours were as follow: WSA-61%, RAA-55%, LDC-72%, BFI-66% and LIP-40% respectively. These values were found to be comparable to that of ketoprofen-63%. The study showed that the anti-inflammatory properties attributable to these plants may be due to their saponins contents.